Application of Triple Shehu Transformation for solving Volterra Integro-Partial Differential Equation - Alkaleeli, Sameehah R. (Journal of Pure & Applied Sciences, 2021)
This paper depends on some concepts related to the triple Shehu transform; and how its various properties can be used to solve three-dimensional linear Volterra Integro-Partial Differential Equations; in terms of obtaining the exact solutions. Some examples will be studied to support the effectiveness of this transform.